# what is the answer pf 6x+5+7x+3=12x+4?

Relevance
• Anonymous

6x+5+7x+3=12x+4

Take all values containing x in one side and all the others in the other side:

6x+7x-12x = 4-5-3 (when moving a number from one side to another, we reverse the sign)

6x+7x-12x = 13x-12x= 1x (or x)

4-5-3 = -1-3=-4

therefore x=-4 (:

Bring all the x's on one side, and all the numbers on the other. Always remember that when you bring a quantity from one side to another, you CHANGE ITS SIGN.

6x + 5 + 7x + 3 = 12x + 4

6x + 7x - 12x = 4 - 5 - 3 (Notice how 12x becomes -12x, 5 becomes -5 and 3 becomes -3)

x = -4

I hope that helps. :)

Check: Put x = -4 in the given equation, and check whether LHS = RHS.

6x + 5 + 7x + 3 = 12x + 4

6 (-4) + 5 + 7 (-4) + 3 = 12 (-4) + 4

-24 + 5 - 28 + 3 = -48 + 4

-44 = = -44

LHS = RHS

So x = -4 is correct.

I hope that helps. :)

me07.

Just sum them up:

6x + 7x = 13x, 5+ 3 = 8 ->

13 x + 8 = 12x + 4, make them equal to zero at one side:

13x - 12x + 8 -4 = 0 -> x + 4 = 0 ->

x=-4

• Anonymous

Move all the x to one side and the integers to the other:

6x-12x+7x=4-5-3

x= -4

• ?
Lv 7

First simplify each side by adding the x terms and the whole numbers.

That gives you 13x + 8 = 12x + 4

Then move all the terms in x to one side or the other and do the same with the whole numbers remembering to change the sign when you you do. Thus:

13x - 12x = 4 - 8

x = - 4

You can always check the result by substituting it in the original equation

i don't know what the pf stands for, but if this is just a regular algebra problem it goes like this.

6x + 5 + 7x + 3 = 12x + 4

13x + 10 = 12x + 4 simplify

x + 10 = 4 move x's to one side

x = -6 get x by itself

6x+5+7x+3=12x+4

6x+7x+5+3=12x+4

13x+8=12x+4

13x-12x=4-8

x= -4

• Anonymous

Group all the x's on one side and all the numbers on the other.

12x - 6x - 7x = -x and 5 + 3 - 4 = -2

So you have -x = -2

To finish, solve for positive x by flipping the signs of both sides, leaving

x=2

Source(s): I'm into college-level calculus, I know basic algebra.

group like terms.

6x+7x-12x=4-5-3

13x-12x=4-8

x=-4